2021
DOI: 10.1186/s12885-021-07834-4
|View full text |Cite
|
Sign up to set email alerts
|

A 4-gene signature predicts prognosis of uterine serous carcinoma

Abstract: Background Uterine serous carcinoma (USC) is an aggressive type of endometrial cancer that accounts for up to 40% of endometrial cancer deaths, creating an urgent need for prognostic biomarkers. Methods USC RNA-Seq data and corresponding patients’ clinical records were obtained from The Cancer Genome Atlas and Genotype-Tissue Expression datasets. Univariate cox, Lasso, and Multivariate cox regression analyses were conducted to forge a prognostic si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
6
1
Order By: Relevance
“…Finally, on multivariable Cox proportional hazards regression analysis, the presence of recurrence or metastases to the liver and/or the peritoneum were independently associated with shorter OS regardless of their mutational status, race, ethnicity or other sites of recurrence or metastases. Various studies attempted to build predictive survival models for USC, including a study by Chen et al on 110 women with USC which showed that a combination of mutated genes, a 4-gene signature, was predictive of OS (42). Differently from our study, their model did not include sites of metastases or survival as potential predictors.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Finally, on multivariable Cox proportional hazards regression analysis, the presence of recurrence or metastases to the liver and/or the peritoneum were independently associated with shorter OS regardless of their mutational status, race, ethnicity or other sites of recurrence or metastases. Various studies attempted to build predictive survival models for USC, including a study by Chen et al on 110 women with USC which showed that a combination of mutated genes, a 4-gene signature, was predictive of OS (42). Differently from our study, their model did not include sites of metastases or survival as potential predictors.…”
Section: Discussioncontrasting
confidence: 58%
“…Various studies attempted to build predictive survival models for USC, including a study by Chen et al. on 110 women with USC which showed that a combination of mutated genes, a 4-gene signature, was predictive of OS ( 42 ). Differently from our study, their model did not include sites of metastases or survival as potential predictors.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of KRT23 affects the cell cycle, DNA replication, recombination, and repair (Birkenkamp-Demtröder et al, 2013). Evidence from previous studies has indicated that KRT23 influences the proliferation, migration, and prognosis of cancer (Odena et al, 2016;Zhang et al, 2017;Chen et al, 2021). ANGPT2 is a ligand for TIE1-TIE2 signaling involved in the development and maintenance of blood and lymphatic vessels (Smeland et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 was significantly more expressed in the UCS than in normal control endometrial tissue in USC of TCGA and GETX datasets. Meanwhile, a 4-gene ( KRT23 , CXCL1 , SOX9 , and ABCA10 ) signature robustly predicts OS and recurrence-free survival(RFS) of USC ( 81 ). Furthermore, the expression of both mRNA and protein of SOX9 was significantly higher in tumor tissues than in paired adjacent tissues.…”
Section: Endometrial Cancermentioning
confidence: 99%